Pengaruh Harga, Kualitas Pelayanan, dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Ulang Tiket Pesawat Berbasis Teknologi (Studi Kasus Pengguna Travel Agent Pegipegi.Com di Yogyakarta) - Arif Fakhrudin; Habib Darul Aminuddin (PT FORMOSA CENDEKIA GLOBAL, 2022)
At this time, globalization has resulted in the existing technology experiencing a fairly rapid development and its sophistication exceeds that of previous years. The rapid growth of globalization can be seen with the use of the internet which gives an active role in activities in human life. Utilization of the internet is used as an intermediary in communication, entertainment facilities, and e-commerce and is also known as electronic commerce. Before there was an online booking service, in the past, the ticket purchase process could only be carried out at travel agents or airline companies located in special places. This will take quite a lot of time spent and the prices provided vary This study aims to determine the effect of price (X1), service quality (X2), consumer trust (X3) on the decision to repurchase (Y) technology-based airline tickets (a case study of pegipegi.com users in Yogyakarta). This research was conducted based on the development of information technology in Indonesia. The number of respondents used were 100 people with purposive sampling method. The analytical method used is multiple linear regression. The results show that price (X1) has a significant effect on online ticket purchasing decisions at pegipegi.com, as well as service quality (X2), and consumer trust (X3) has a significant effect on repurchase decisions. at pegipegi.com. this shows that pegipegi.com consumers already believe that the services and tickets sold are relevant to the price offered. Price (X1) has a significant influence on the decision to re-purchase airline tickets (Y) online at pegipegi.com. Service quality (X2) has a significant influence on the decision to re-purchase airline tickets (Y) online at pegipegi.com